REFLEKSI KRITIS TERHADAP KARYA KESELAMATAN ALLAH DALAM KERANGKA HISTORIS KITAB SUCI PERJANJIAN LAMA - Fransesco Agnes Ranubaya; Gregorius Tri Wardoyo (Bahasa Indonesia, 2022)
The focus of the study discussed is the work of God's salvation in a historical framework. In the context of the Old Testament, all events, both wars and trials faced by the Israelites, were God's plans that had been prepared. The historical God is present in the form of justice which ultimately provides salvation for mankind. The writing of this scientific paper uses the method of critical analysis with reflection and relevance through the correspondence truth test. The purpose of writing this article is to take a deeper look at how great and extraordinary the works of God's salvation were in the history of the people of Israel. Furthermore, it is also explained how God makes various efforts so that His chosen people are always directed to Him, things that make the Israelites fall into sin and come to a reflection on God's loving works of salvation in forgiving people's sins. This article outlines how deep God's love for the Israelites is in the life history of God's chosen nation. The benefit of writing this article is to reflect more deeply that God's love is so real in human life.